FROM AD HOC ISSUE PUBLICS TO DISCOURSE COMMUNITIES: A YEAR OF PUBLIC DEBATE ON TWITTER - Dehghan, Ehsan (AoIR Selected Papers of Internet Research, 2018)
This paper presents an empirical investigation of the concept of ad hoc issue publics, through a mixed-methods analysis of a year of debate over a contentious topic in the Australian public sphere. Following two controversial racial discrimination cases in 2016, a number of Australian conservative politicians called for amendments to a specific section of the Racial Discrimination Act (Section 18C), which they claimed restricted freedom of speech. Similar proposals had been put forward and shelved in 2013. The issue was discussed widely on Twitter and other social media platforms. Eventually, the Australian Senate voted down changes to section 18C. Using a range of network analyses, examining the various network structures created by Twitter’s affordances, this study identifies the publics and communities involved in the debate. The discourses of these communities are then qualitatively analysed. The findings show that different—and sometimes antagonistic—discourse communities are involved in the debate, and while all of these use the same hashtags and keywords, they have contrasting discursive positions. This paper argues that in this case, the publics created as a result of the affordances of Twitter cannot be regarded as ad hoc issue publics, since the discourse communities involved were formed as a result of a priori ideological affinities. Broadly, the findings of this study help in the theorisation of online publics and communities, particularly the necessary elements involved in the formation of ad hoc issue publics and/or online discourse communities.